Linear Phenylsilanes with PSi4P, PSi5P, and Si7 Backbones. Issue 14 (1st April 2022) - Friebel, Mike; Böhme, Uwe; Kroke, Edwin
Abstract: Linear α, ω‐diphosphaoligosilanes were prepared starting from 1, 5‐dilithiodecaphenyl‐ n ‐pentasilane, Li(SiPh2 )5 Li, and chlorodiorganophosphanes. The compounds 1, 5‐bis(diphenylphosphanyl)decaphenyl‐ n ‐pentasilane, (Ph2 P)Si5 Ph10 (PPh2 ), 1, 5‐bis(di‐ iso ‐propylphosphanyl)decaphenyl‐ n ‐pentasilane, ( i Pr2 P)Si5 Ph10 (P i Pr2 ), and 1, 4‐bis(di‐ iso ‐propylphosphanyl)octaphenyl‐ n ‐tetrasilane, ( i Pr2 P)Si4 Ph8 (P i Pr2 ), were obtained in moderate to good yields and characterized with IR‐, Raman‐, UV‐, 31 P‐, 29 Si‐, and 1 H‐NMR spectroscopy. Single crystal structure analyses of these three silanes show all‐transoid conformations of the atoms along the phosphorus‐silicon backbone of the molecules in the solid state. The silicon‐silicon and the silicon‐phosphorus‐bonds are elongated. This is caused by the complete substitution of these molecules by sterically demanding phenyl‐ and i ‐propyl‐substituents and effective σ‐conjugation along the main chains. Hexadecaphenyl‐ n ‐heptasilane, Si7 Ph16, was prepared for comparison with the other three compounds. The latter one shows a long wavelength UV‐absorption in the same region as 1, 5‐bis(diphenylphosphanyl)decaphenyl‐ n ‐pentasilane. Abstract : Elongated Si−Si and Si−P bonds are observed in linear phenylsilanes with PSi4 P and PSi5 P backbones (left). This is caused by effective σ‐conjugation and the complete substitution of these molecules by sterically demanding phenyl substituents. The crystal structure analyses of three α, ω‐diphosphaoligosilanes revealed slowly winding helices of the main chain (right).